Knowledge, certainty, and assertion. (17th February 2016) - Turri, John
Abstract : Researchers have debated whether knowledge or certainty is a better candidate for the norm of assertion. Should you make an assertion only if you know it's true? Or should you make an assertion only if you're certain it's true? If either knowledge or certainty is a better candidate, then this will likely have detectable behavioral consequences. I report an experiment that tests for relevant behavioral consequences. The results support the view that assertability is more closely linked to knowledge than to certainty. In multiple scenarios, people were much more willing to allow assertability and certainty to come apart than to allow assertability and knowledge to come apart.